Goal orientation based relationship between coaching efficiency, athlete satisfaction, and team cohesion - Khorram, M. H. (Scientific Journal of Sport and Performance, 2023)
In this study, the mediating role of goal orientations in the relationship between a coach-athlete relationship (CAR) and collective effectiveness (CE), based on the results between the coaching efficiency variables, athlete satisfaction, and team cohesion was investigated. Participants were 252 professional athletes from four different sports. Data were obtained using questionnaires on coaching performance, athlete satisfaction, and team cohesion. Structural equation modelling showed that CAR has a positive indirect effect on athlete satisfaction and a positive direct effect on team cohesion. Athletes' satisfaction also had both direct and indirect positive effects on team cohesion. Also, the coaching effectiveness had the greatest effect on group cohesion. Coaches can use strategies and stimuli that create a sense of satisfaction in athletes and lead them to appropriate, professional, and athletic behaviour. The results show that a good quality CAR increases athletes' focus on their goals and develop their individual skills, thus improving team performance.